Isotopic and genetic analyses of a mass grave in central California: Implications for precontact hunter‐gatherer warfare. Issue 1 (2nd September 2015) - Eerkens, Jelmer W.; Carlson, Traci; Malhi, Ripan S.; Blake, Jennifer; Bartelink, Eric J.; Barfod, Gry H.; Estes, Alan; Garibay, Ramona; Glessner, Justin; Greenwald, Alexandra M.; Lentz, Kari; Li, Hongjie; et al.
ABSTRACT: Objectives: Analysis of a mass burial of seven males at CA‐ALA‐554, a prehistoric site in the Amador Valley, CA, was undertaken to determine if the individuals were "locals" or "non‐locals, " and how they were genetically related to one another. Methods: The study includes osteological, genetic (mtDNA), and stable (C, N, O, S) and radiogenic (Sr) isotope analyses of bone and tooth (first and third molars) samples. Results: Isotopes in first molars, third molars, and bone show they spent the majority of their lives living together. They are not locals to the Amador Valley, but were recently living to the east in the San Joaquin Valley, suggesting intergroup warfare as the cause of death. The men were not maternally related, but represent at least four different matrilines. The men also changed residence as a group between age 16 and adult years. Conclusions: Isotope data suggest intergroup warfare accounts for the mass burial. Genetic data suggest the raiding party included sets of unrelated men, perhaps from different households. Generalizing from this case and others like it, we hypothesize that competition over territory was a major factor behind ancient warfare in Central California. We present a testable model of demographic expansion, wherein villages in high‐population‐density areas frequently fissioned, with groups of individuals moving to lower‐population‐density areas to establish new villages. This model is consistent with previous models of linguistic expansion. Am J Phys Anthropol 159:116–125, 2016. © 2015 Wiley Periodicals, Inc.